"Wilderness" revisited: Is Canadian park management moving beyond the "wilderness" ethic?. (11th February 2020) - Youdelis, Megan; Nakoochee, Roberta; O'Neil, Colin; Lunstrum, Elizabeth; Roth, Robin
Abstract : This paper questions whether the rescaling of conservation practice in Canada to include local and Indigenous communities, NGOs, and private market‐based actors represents a move away from wilderness‐thinking in conservation, and what implications this might have for the future of conservation in Canada. We explore the links between Cronon's "wilderness" ethic and coloniality, racism/sexism/classism, and political economy, and the extent to which recent trends in conservation practice, such as co‐management arrangements, private tourism proposals, and a shift in programming to attract a diverse public to parks, help us to move beyond the limited vision for conservation and environmentalism that the wilderness ethic provides. We interrogate the ways in which the concept of wilderness is being employed, resisted, and transformed by a multitude of actors in three parks and conservation areas across Canada. We argue that although recent developments in conservation practice help to redress some of the worrisome aspects of wilderness‐thinking in parks, they also reinforce and re‐emphasize problematic lines of thinking and praxis. While the wilderness character of Canadian parks has shifted a great deal since the turn of the 20 th century, the wilderness ethic remains deeply embedded within conservation discourse and practice. Key Messages: Cronon's critique of the wilderness ethic has been foundational to critical literature on conservation in Canada. The rescaling of conservation to include Indigenous communities, NGOs, and private interests in some ways represents a departure from wilderness‐thinking in conservation. Despite advances made, a problematic wilderness ethic remains deeply embedded within conservation discourse and practice. Le concept de « milieu naturel » réexaminé : est‐ce que la gestion des parcs canadiens va au‐delà de l'idéologie de la « nature sauvage »?: Le présente texte s'interroge à savoir si le réorganisation des pratiques de conservation au Canada pour inclure les communautés autochtones et locales, les ONG et les acteurs du marché privé constitue un virage par rapport au concept de nature sauvage et, si oui, quelles en sont les conséquences pour l'avenir de la conservation au Canada. Plus précisément, nous étudions les liens entre l'idélologie de la « nature sauvage » de Cronon et la pensée coloniale, le racisme/sexisme/classicisme et l'économie politique ainsi que l'importance des tendances récentes en matière de conservation, démarches qui nous aident à aller au‐delà de la vision limitée de la conservation et de l'environnementalisme que propose l'idéologie de la nature sauvage. Ces tendances récentes sont les arrangements de cogestion, les propositions de tourisme privé de même que les changements dans la programmation pour attirer un public diversifié dans les parcs. Nous analyserons aussi les façons dont le concept de nature sauvage est utilisé, contrecarré et transformé par une multitude d'acteurs dans trois parcs et aires de conservation du Canada. Nous soutenons que même si les progrès récents dans les pratiques de conservation contribuent au redressement de certains aspects préoccupants de l'idéologie de la nature sauvage dans les parcs, ils renforcent et réaffirment également ce mode de pensée dans la recherche et la pratique. Au final, bien que le contexte biophysique des parcs canadiens ait énormément changé depuis le tournant du 20 e siècle, l'idéologie de la nature sauvage demeure profondément ancrée dans les discours et les pratiques de conservation.